2014
DOI: 10.1038/cdd.2014.67
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of calbindin-D28k in the pathogenesis of Alzheimer’s disease mouse model

Abstract: Calbindin-D28k (CB), one of the major calcium-binding and buffering proteins, has a critical role in preventing a neuronal death as well as maintaining calcium homeostasis. Although marked reductions of CB expression have been observed in the brains of mice and humans with Alzheimer disease (AD), it is unknown whether these changes contribute to AD-related dysfunction. To determine the pathogenic importance of CB depletions in AD models, we crossed 5 familial AD mutations (5XFAD; Tg) mice with CB knock-out (CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 59 publications
5
72
0
2
Order By: Relevance
“…Supporting this notion, Popović et al (2008) observed preservation of CB-IR in the most caudal part of molecular and granular layers of the DG in APPswe/PS1dE9 mice coinciding with a decrease in Aβ deposition. Recently, using CBdeficient AD transgenic mice (CBKOTg), (Kook et al, 2014) demonstrated that CB depletion contributes to Aβ-induced apoptosis and neurodegenerative changes in the brain.…”
Section: Calbindin Immunoreactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this notion, Popović et al (2008) observed preservation of CB-IR in the most caudal part of molecular and granular layers of the DG in APPswe/PS1dE9 mice coinciding with a decrease in Aβ deposition. Recently, using CBdeficient AD transgenic mice (CBKOTg), (Kook et al, 2014) demonstrated that CB depletion contributes to Aβ-induced apoptosis and neurodegenerative changes in the brain.…”
Section: Calbindin Immunoreactivitymentioning
confidence: 99%
“…CB mediates biological effects such as synaptic transmission, protein synthesis, and also plays a role in neuronal vulnerability (Iritani et al, 2001). In addition it has been shown to block multiple pro-apoptotic pathways, and overexpression of CB has been related to glial and neuronal protection from Aβ and mutant presenilin-1 (PS1) (Kook et al, 2014). Therefore, the increase in CB-IR observed in APPswe/PS1dE9 mice at an early stage (3 months) in hippocampal areas suggests an attempt of this protein to control the deregulated cell homeostasis and to protect against the formation of neurofibrillary tangles or senile plaques as was suggested by Iritani Fig.…”
Section: Calbindin Immunoreactivitymentioning
confidence: 99%
“…Although Са 2+ sensors regulate the activities of ion channels and enzymes, Са 2+ buffers modulate the amplitude and kinetics of free Са 2+ transients and maintain Са 2+ homeostasis. For example, Са 2+ buffers keep the concentration of free Са 2+ below the levels that would induce cell death (Christakos and Liu, 2004;D'Orlando et al, 2001;Kook et al, 2014). Because the affinity of tescalcin for Ca 2+ is in the micromolar range (Gutierrez-Ford et al, 2003), it is thought to be a Са 2+ -sensor.…”
Section: +mentioning
confidence: 99%
“…Moreover, different calcium channel blockers have been reported to be effective in preventing long/short-term memory impairment induced by A [25][26][27][28][29][30][31][32][33][34][35] [38]. Individuals with AD have a down regulation of the expression of the Ca 2+ buffering protein calbindin which aids in restricting the Ca 2+ amplitude thus regulating Ca 2+ signalling [39].In addition, activated Aα 42, a specific amyloid plaque, carries out Ca 2+ cellular responses allowing Ca 2+ influx that induces excitotoxicity [40]. Given the ubiquitous involvement of Ca 2+ dysregulation in AD, it logically presents a variety of potential therapeutic targets for AD prevention and treatments.…”
Section: Discussionmentioning
confidence: 99%